Recent Advances in Chronic Renal Failure: A Review of Integrated Traditional Chinese and Western Medicine Perspectives - Yan, Zilong; Tian, Yun (Journal of Contemporary Medical Practice, 2026)
Chronic renal failure (CRF), the common end-stage outcome of progressive chronic kidney diseases, is characterized by irreversible decline in glomerular filtration rate and multisystem complications. With over 840 million affected individuals worldwide, CRF poses a major public health challenge. In recent years, mechanistic research on CRF has expanded from traditional hemodynamic abnormalities and fibrotic drivers to encompass immunoinflammatory regulation, mitochondrial energy metabolism reprogramming, and gut-kidney axis dysbiosis. Biomarker studies have focused on the value of tubular injury markers (KIM-1, NGAL) and inflammatory mediators (TNF-α, IL-6) in early diagnosis and prognostic assessment. In terms of therapeutic strategies, accumulating evidence supports the use of SGLT2 inhibitors, nonsteroidal mineralocorticoid receptor antagonists, and GLP-1 receptor agonists, while traditional Chinese medicine interventions—including rhubarb preparations, Cordyceps mycelial products, and blood-activating and stasis-resolving formulas—have garnered increasing attention for their adjunctive roles in slowing renal function decline. This review systematically synthesizes these advances and critically evaluates current research bottlenecks and translational prospects, aiming to inform clinical decision-making and future investigations.